LEGAL PROTECTION OF CHILDREN OUT OF MARRIAGE REGARDING THE ACQUISITION OF INHERITANCE RIGHTS BASED ON CUSTOM MARRIAGE ACCORDING TO INDONESIAN LEGAL PERSPECTIVE - Illie Vicario; Vincent De Paul; Herman Brahmin; Vonny Armin (Awang Long Law Review, 2023)
Marriages are carried out in accordance with applicable customary provisions and the religion adopted is legal according to the Indonesian law. The research method that was used was a qualitative research method. However, this customary and religious marriage without registering it in the Civil Registration is still legal under the law, but it will have an impact on the legal consequences of the child being born. These children will be born with the status of illegitimate child for law administration. This will cause problems in the distribution of inheritance to these children. These children still have thev thev opportunityv to inherit thev propertyv ofv theirv parentsv, if v they varevrecognizedvbyvtheirvfathervand mother. At the same time, they can inherit their mother's property directly in accordance with the law without any acknowledgment at all, because the name listed on their Birth Certificate is a valid proof of heir. Even though they were born as illegitimate children, they are the heirs who are prioritized as the First Class of Heirs. Therefore, legal protection for illegitimate children is needed for their right to receive their parents' inheritance. The result inheritance law protection for children out of wedlock is regulated carefully in the Civil Code, which then the status of children out of wedlock becomes stronger with the existence of Article 43 UUP. The status of this illegitimate child becomes the same as the heir to the first class.